Uji Daya Hambat Ekstrak Daun Sirih Hutan (Piper aduncum L.) Terhadap Pertumbuhan Bakteri Streptococcus mutans - Nunung Safriana; Orryani Lambui; Ramadanil Ramadanil (Biology Department, Mathematics and natural science, Tadulako University, 2019)
The research about inhibition test of leaf extract of Piper aduncum L. to the growth of bacteria Streptococcus mutans have been conducted during periods of July to December 2016, on aim of this research was to study the inhibition test from leaf extract of P. aduncum L. the growth of the bacteria S. mutans and the amount of compound contained in the leaf of P. aduncum L. The extraction method was used is maseration method and testing of the inhibition of the extract to the bacteria S. mutans by disc diffusion method. This research is compiled in a completely randomized designed (CRD) with 6 treatments and 3 replications. The treatments were leaf extract concentration 30%, 45%, 60%, 75%, antibiotic Tetracycline hydrochloride 5% as the positive control and negatif control aquades. The results showed that the concentrations of leaf extract 75% produced the greatest inhibition zone is 13,1 mm. this indicates tha the leaf extract of P. aduncum L. have inhibitory better. Phytochemical screening results showed that there were compound flavonoid, tannin, saponin and alkaloid that can inhibit the growth of bacteria.